A Novel Approach to Solve Quasiexactly Solvable Pauli Equation. (29th January 2015) - Koç, Ramazan; Olğar, Eser; Mutaf, Haydar
Abstract : The spectra for some specific forms of external magnetic fields in Pauli equation are obtained in the framework of the asymptotic iteration method (AIM). AIM is applied to find the solution of Pauli equation. When the method is applied to quasiexactly solvable systems, it not only easily gives the corresponding spectrum, but also produces accurate results for the eigenvalues of the system having sl (2) symmetry.